(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
This article examines the formation and development of Anthropology in Kyrgyzstan, as well as the contribution of Academician Abylabek Asankanovich Asankanov to its institutionalization and promotion. The author analyzes three main stages of the development of anthropology in the country: the pre-revolutionary period, the Soviet period, and the post-Soviet era. Special attention is given to establishing the national anthropological school, opening the dissertation committee